USE OF HEURISTIC METHODS IN IMPROVING THE EDUCATIONAL PROCESS - Kodirov, Gayrat (Журнал иностранных языков и лингвистики, 2024)
The integration of heuristic methods in education has proven to be an effective approach in fostering critical thinking, problem-solving, and independent learning among students. Unlike traditional, directive methods, heuristic techniques encourage exploration, self-directed inquiry, and the development of unique solutions. This article examines the role of heuristic methods in improving the educational process, highlighting their impact on student engagement and cognitive development. Through a review of recent studies and practical applications, this paper demonstrates how heuristic strategies support knowledge retention and adaptability, thereby equipping students with the skills necessary for real-world challenges. The findings underscore the value of heuristic methods as transformative tools that enhance not only academic achievement but also lifelong learning skills.